Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/ece3.7425
|View full text |Cite
|
Sign up to set email alerts
|

Individual‐level leaf trait variation and correlation across biological and spatial scales

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…In our case, the trait alignment with the first PCA axis also reflects the conservative/acquisitive nature of the leaf traits in broadleaved trees. The acquisitive traits SLA, leaf P and the cations aligned closely with the first PCA axis, which is consistent with previous studies showing similar relationships at the species level (Lin et al 2020, Jiang et al 2021. Furthermore, the conservative traits LDMC and leaf C were negatively aligned with the first PCA axis, which is also in agreement with previous studies (Lin et al 2020, Jiang et al 2021.…”
Section: Coordination Of Leaf Traits At the Within-individual Levelsupporting
confidence: 91%
“…In our case, the trait alignment with the first PCA axis also reflects the conservative/acquisitive nature of the leaf traits in broadleaved trees. The acquisitive traits SLA, leaf P and the cations aligned closely with the first PCA axis, which is consistent with previous studies showing similar relationships at the species level (Lin et al 2020, Jiang et al 2021. Furthermore, the conservative traits LDMC and leaf C were negatively aligned with the first PCA axis, which is also in agreement with previous studies (Lin et al 2020, Jiang et al 2021.…”
Section: Coordination Of Leaf Traits At the Within-individual Levelsupporting
confidence: 91%
“…mollissima are scientifically evaluated, they can be assessed on the basis of correlation analysis of these traits, which can intuitively reflect the relationships between them. Correlation analysis is applied to determine the degree of correlation between two or more correlated variables [ 27 ]. In this study, 15 and 16 pairs of fruit phenotypic and quality traits showed extremely significant positive correlations (P<0.01) and significant positive correlations (P<0.05), respectively, and 4 and 15 pairs showed extremely significant negative correlations (P<0.01) and significant negative correlations (P<0.05), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Niu et al showed that the importance of ITV in plant communities increased with environmental harshness in alpine meadows in Tibet [16]. One study using a large dataset of 10 leaf and petiole traits in temperate forest seedlings found that about 40% of trait variation was explained by intraspecific variation [17]. In conclusion, these findings suggest that using mean values for functional traits ignores actual trait variation and that the effect of intraspecific variation on functional diversity varies among ecosystems.…”
Section: Introductionmentioning
confidence: 88%